2008
DOI: 10.1371/journal.pone.0001530
|View full text |Cite
|
Sign up to set email alerts
|

mtDNA nt13708A Variant Increases the Risk of Multiple Sclerosis

Abstract: BackgroundMitochondrial DNA (mtDNA) polymorphism is a possible factor contributing to the maternal parent-of-origin effect in multiple sclerosis (MS) susceptibility.Methods and FindingsIn order to investigate the role of mtDNA variations in MS, we investigated six European MS case-control cohorts comprising >5,000 individuals. Three well matched cohorts were genotyped with seven common, potentially functional mtDNA single nucleotide polymorphisms (SNPs). A SNP, nt13708 G/A, was significantly associated with MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 31 publications
8
55
0
7
Order By: Relevance
“…We showed that the mtDNA variations could affect susceptibility to EAE. This observation is consistent with those in humans, in which mtDNA variations are associated with susceptibility to MS (Yu et al 2008). Our results provide confirmatory evidence for the role of mitochondria in MS.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We showed that the mtDNA variations could affect susceptibility to EAE. This observation is consistent with those in humans, in which mtDNA variations are associated with susceptibility to MS (Yu et al 2008). Our results provide confirmatory evidence for the role of mitochondria in MS.…”
Section: Discussionsupporting
confidence: 92%
“…The C57BL/6J strain is used widely for induction of EAE by immunization with MOG 53-55 peptides. In humans, it has been suggested that mtDNA variations affect susceptibility to MS (Yu et al 2008). Therefore, we investigated the effect of mtDNA variants on EAE.…”
Section: Effects Of Mtdna Variants On Eaementioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria contain their own 16-kb genome, the mitochondrial DNA (mtDNA), which encodes 37 genes, 13 proteincoding genes as well as 22 tRNA and 2 rRNA genes (2). Variations in mtDNA affecting OXPHOS functions may cause mitochondrial dysfunctions and have been reported to associate with complex diseases, including chronic inflammation and autoimmune diseases, for example systemic lupus erythematosus (5) and multiple sclerosis (6).…”
Section: Introductionmentioning
confidence: 99%
“…The less frequent A allele that is associated with an increased expression of the UCP2 gene transcript had a protective effect on the risk for developing MS in our earlier study. 4 We have also confirmed and extended the earlier reported associations between mtDNA variants and MS, 5 we identified the mtDNA nt13708A variant as a risk allele for MS. 6 In this study, we aimed to investigate the two aforementioned MS-associated mitochondrial variants in other chronic inflammatory diseases. That is, we tested UCP2 -866 G/A and mtDNA nt13708 G/A for an association with eight distinct chronic inflammatory diseases, which included rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), Wegener' granulomatosis (WG), Churg-Strauss syndrome (CSS), Crohn's disease (CD), ulcerative colitis (UC), primary sclerosing cholangitis (PSC) and psoriasis.…”
Section: Introductionmentioning
confidence: 99%